Auto-calibration of capacitive MEMS accelerometers based on pull-in voltage - Rocha, Luís A. (2011)
This paper describes an electro-mechanical auto-calibration technique for use in capacitive MEMS accelerometers. Auto-calibration is achieved using the combined information derived from an initial measurement of the resonance frequency and the measurement of the pull-in voltages during device operation, with an estimation of process-induced variations in device dimensions from layout and deviations in material properties from the known nominal value. An experiment-based analytical model is used to compute the required electrostatic forces required to simulate external accelerations allowing the electro-mechanical calibration of the accelerometer. Measurements on fabricated devices confirm the validity of the proposed technique and electro-mechanical calibration is experimentally demonstrated.